Service Delivery Transformation for UHC in Asia and the Pacific - Gerald Bloom (Taylor & Francis Group, 2019)
This article was drafted as part of a review of strategies for making progress toward universal health coverage in the countries of Asia and the Pacific. It focuses on strengthening the delivery of services, in the context of population aging. It argues that it is important to take into account big differences in development contexts and also the rapid, interconnected changes that many countries are experiencing. The article focuses especially on countries with relatively undeveloped institutions and pluralistic and highly segmented health sectors. It argues that attempts by these countries to import institutional arrangements from outside are likely to be complicated. It argues that government needs to focus on both short-term measures to meet immediate needs and the longer-term aim of establishing effective institutional arrangements. This means that they need to take into account the political factors that influence the direction of health system change. The article emphasizes the need to strengthen the capacity of the health system to address the growing challenge of chronic noncommunicable diseases to avoid heavy political pressure to expand hospital services. It then explores the opportunities and challenges associated with the rapid expansion of digital health services. It concludes with a discussion of government stewardship and management of health system transformation to address the major challenges associated with population aging.